Higher Order Fractional Variational Symmetric Duality Over Cone Constraints - Khatri, Sony; Prasad, Ashish Kumar (Yugoslav Journal of Operations Research, 2022)
The article aims at higher order fractional variational pair of symmetric dual formulations where constraints are defined over cones and explores pertinent duality output applying the idea of higher order $η$-invexity. Also, we bring into begin a numerical example in order to validate the definition exploited to establish duality results. Moreover, we demonstrate a case study dealing with the static formulation of our considered problem and explore the results carefully.